Pengaruh Model Problem Based Learning terhadap Minat Belajar Peserta Didik di Sekolah Dasar - Ensuriati, Ensuriati (Asian Journal of Early Childhood and Elementary Education, 2024)
Interest in learning is one of the factors that can influence student learning outcomes. In the learning process we often encounter problems related to students. In this study, researchers found the problem of students who were less active in learning activities. So researchers try to provide a solution so that students' interest in learning increases, namely by using the Problem Based Learning model. The aim of this research is to determine the influence of the Problem Based Learning model on students' interest in learning in elementary schools. This research uses the Systematic Review Literature method. Researchers searched for relevant articles on the Google Scholar database, by looking for articles that were relevant to the topic. From several articles found, 10 articles from 2019-2024 were found that were relevant to the topic of the Problem Based Learning model on students' learning interest in elementary schools. Based on several of these articles, the results showed that there was an increase in students' interest in learning using the Problem Based Learning model compared to the conventional model. This means that there is an influence between the use of the Problem Based Learning model and students' interest in learning in elementary schools.